Принципи об`ємно-розпланувального та образного вирішення мансардних поверхів багатоквартирних будинків на прикладі Відня - Попович, С. Р. (Видавництво Львівської політехніки, 2016)
Розглядаються основні принципи об’ємно-планувального та образного вирішення мансардних поверхів, влаштованих на горищних поверхах багатоквартирних будинків, на прикладі натурних обстежень, фотофіксацій та аналізу вирішення мансардних поверхів багатоквартирних будинків у м. Відень, Австрія. Подано рекомендації щодо проектування мансардних поверхів залежно від типу та стилістики оточуючої забудови. Lviv is a city with a rich historical architectural heritage, but it is also a city that is currently growing. Therefore, it is needed a special comprehensive approach to solve problems associated with the reconstruction of attic floors. The analysis of existing mansard and attic floors shows noticeable lack of general harmonious imaginative solutions, primarily due to the completion of chaos, neglect attic floors, usage of different materials and colors coverings. By the way,gv civen the strong demand among residents for placement attics, reconstruction of attic floor is one of the main methods of revitalization of the urban environment. This article discusses the basic principles of volumetric solution and imaginative solutions of mansards, arranged in attic floors of apartment buildings located in the existing built environmenton the example of the results of field surveys, photofixation and analysis of solutions of attic floors of apartment buildings in Vienna, Austria. Roofs form a silhouette of the city, but factors such as chaotic partial reconstruction of attics, design excluding architectonics of surrounding buildings, the use of different types of coating, finishing materials, etc. destroys the harmony of the silhouette of the city. In the paper are listed recommendations for the design of attic floors, depending on the type and style of the surrounding buildings. For example, it is recommended to rehabilitate the whole story, not just part of it, especially given the composition of the building and its location in the street structure. The approaches to scale of reconstruction are various for buildings of different eras. Thus, for historic buildings, protected by UNESCO, it is advisable to renovate the attic floor to the roof volume to improve technical and economic performance, energy-saving buildings, replacement of roof coverings in the same style.The building of 19-20 centuries which is not a monument of architecture, it is permissible to include new volumes, change the shape of the roof, to arrange terraces, landscaping and more. In terms of lack of free sites for new construction in the city, attic reconstruction can become an alternative source of increasing in housing stock, will improve the technical condition of the building and will become part of the revitalization of areas that are in decline.
Principles of volumetric and imaginative solutions of attics ofapartment buildingson the example of Vienna
Keywords: мансарда; реконструкція горища; образне вирішення; mansard; attic renovation; imaginative solutions; 7.032:72.01:72.032